Perceptions of nursing as a future profession among high school students’ females in AL-RASS city, Saudi Arabia - Al-humaidan, Arwa; Mersal, Fathia (International Journal of Advanced Nursing Studies, 2017)
Background: Saudi Arabia has a huge shortage of Saudi nurses. Therefore, the students’ perception of nursing affect their future choice of nursing career. Despite nursing is an honorable profession the majority of Saudi’s families still do not think like that about nursing.Aim: This study aimed to explore the Perceptions of nursing as a future profession among Secondary school students' females in Al Rass city KSA.Design: A cross-sectional descriptive design was utilized.Sample: A convenient sample of female’s secondary school was included.Tools: Professional nursing perception questionnaires were used and provided to 225 females aged 16 and above who are attending the largest 4 high governmental schools in Al-Rass city in the Qassim region of KSA.Result: the result revealed that almost all had an idea about the functional aspect of nursing career, and 37% of them have got this infor-mation from media. However, only 29% of participants will choose nursing as a future career. Additionally, 55.1% of participants indicated that nursing requires science background that was their primary reason to avoid nursing career.Conclusion: this study concluded that the majority of respondents do not prefer nursing as future career. Therefore, there is a critical need to enhance the image of nursing and attract more high school students into this profession.